(3adSaJgG hCSGdjH JNWjWgG hCOhGJ bjGSgG s - (3YKeGf eMeO(B, (3Zfjes; (3eGLO CMeO CHh RfW(B, s ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY,s, 2010)
(3GdeYfi GddZhj hGdeaghe GdYdej ddJfejI GdeSJOjeI, CHYGO GdJfejI GdeSJOjeI, GdKbGaI GdEbJUGOjI GdSGFOI hGdJfejI GdeSJOjeI, GdJfejI GdeSJOjeI hCReI KbGaI Ce CReI HjFI, GdESJTYGQ Yf HYO hfXe GdeYdheGJ GdLZQGajI hGdJfejI GdeSJOjeI, HYV GdCSGdjH GdHjFjI GdeTLYI aj GdJNWjW , bjGS GdJfejI GdeSJOjeI, GdJLQHI GdCQOfjI aj eLGd GdJNWjW hGdJfejI hGdeMGaXI Ydi GdHjFIs
Keywords: (3GdJNWjW GdELJeGYjs; (3GdJNWjW GdEbJUGOjs; (3GdJfejIs